Perovskite solar cell using single-walled carbon nanotube as transparent conductive electrode and method of manufacturing the same
Patent Information
- Application Number
- JP2023127452
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
AI Technical Summary
【0015】 以上説明したように、本発明に使用するペロブスカイト太陽電池の透明導電性電極は、一般的に使用されているITOガラスと比較して、柔軟性、導電性、光透過性に優れた単層カーボンナノチューブに置き換えることができ、これにより本発明では、低い製造コストで柔軟性、導電性、光透過性に優れ、しかも薄く、軽量で、曲げや変形にも優れているなどの利点を有するペロブスカイト太陽電池を提供できる。
Smart Images

Figure 2025023385000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a perovskite solar cell in which single-walled carbon nanotubes are used as a transparent conductive electrode, and a method for manufacturing the same. [Background technology]
[0002] Perovskite solar cells are a new type of solar cell that uses perovskite crystal structure materials. They are attracting attention because they are inexpensive to manufacture, do not require rare metals, are "light," "thin," and "soft," and are flexible and can be adapted to a variety of shapes. Moreover, they achieve high conversion efficiency comparable to "silicon-based solar cells" and "compound solar cells."
[0003] The rare metal indium tin oxide (ITO) is used as the transparent conductive electrode for perovskite solar cells, but it is expensive, its supply is unstable, and there are problems with the flexibility of ITO conductive glass. The resistance value of ITO conductive glass containing the rare metal indium is 2Ω / sq to 1000Ω / sq, and its light transmittance is only 50% to 90%, making it difficult to achieve low resistance and high light transmittance. As it is difficult to achieve low resistance and high light transmittance, there is an urgent need to consider alternative materials. [Prior art documents] [Patent documents]
[0004] Patent No. 2022-181466 Summary of the Invention [Problem to be solved by the invention]
[0005] The objective of the present invention is to develop a transparent conductive electrode that can replace ITO and a perovskite solar cell equipped with the electrode.
[0006] Carbon nanostructures, which are structures that have a specific microstructure mainly composed of carbon, are known. Such carbon nanostructures include fullerenes, carbon nanotubes, carbon nanowalls, and graphene.
[0007] Of these, carbon nanotubes have a single-wall structure and are SP 2 It is made up of carbon atoms bonded in a honeycomb pattern, with carbon atoms one atom thick, making it flexible and with an electron mobility of 200,000 cm at room temperature. 2 V -1 s -1 ,Resistance value: only 1*10 -4 Ω / sq, light transmittance: 90%~92%.
[0008] Therefore, although carbon nanotubes are theoretically the most ideal transparent conductive material, a uniform carbon nanotube thin film could not be obtained by the synthesis method using the conventional horizontal thermal CVD apparatus, and carbon nanotubes were not suitable as a conductive material.
[0009] In response to this, the inventors' research has revealed that by using a vertical thermal CVD apparatus with a quartz tube installed on the thermal CVD apparatus, atomized Fe / ethanol gas is heated to a specified temperature (800°C to 1000°C) from a nebulizer device and sprayed toward a protective glass (set temperature of about 100°C) placed underneath, where the carbon nanotubes (SWNTs) can be uniformly synthesized into an extremely flat carbon nanotube net on the surface of the protective glass. [Means for solving the problem]
[0010] Based on the above findings, the present invention proposes a perovskite solar cell and a manufacturing method thereof, in which a protective glass is provided at the bottom of a vertical thermal CVD apparatus having an electric furnace installed on the outer periphery, the temperature of the electric furnace of the vertical thermal CVD apparatus is set to 800°C to 1000°C, and a mixed liquid of Fe-based element metal / alcohol is sprayed from a nebulizer device to synthesize one or more single-walled carbon nanotubes onto the protective glass, each of which serves as a transparent conductive electrode.
[0011] Here, examples of Fe-based element metals include Fe, Co, Ni, etc., with Fe being preferred.
[0012] The alcohol may be a lower alcohol such as methanol or ethanol, with ethanol being preferred.
[0013] Under the above conditions, a mixed solution of Fe / ethanol was sprayed from the top of the vertical thermal CVD apparatus using a nebulizer device, whereby a single-walled carbon nanotube net was synthesized on the protective glass placed at the bottom of the apparatus.
[0014] The obtained single-walled carbon nanotube net has an extremely flat carbon nanotube net structure with few defects and large "holes" between the tubes, which allows for flexibility, low resistance and high light transmittance. This effectively increases the absorption of light over a wide spectral range, thereby significantly improving the photoelectric conversion efficiency of perovskite solar cells, making it ideal as a transparent conductive electrode for perovskite solar cells. Effect of the Invention
[0015] As described above, the transparent conductive electrode of the perovskite solar cell used in the present invention can be replaced with single-walled carbon nanotubes, which have superior flexibility, conductivity, and light transparency compared to the commonly used ITO glass. As a result, the present invention can provide a perovskite solar cell that has advantages such as excellent flexibility, conductivity, and light transparency at low production costs, as well as being thin, lightweight, and resistant to bending and deformation. [Brief description of the drawings]
[0016] [Figure 1] A diagram showing an example of a perovskite solar cell according to the present invention in which a single-walled carbon nanotube (SWNTs) net synthesized in a vertical thermal CVD apparatus is used as a transparent conductive electrode. [Diagram 2]FIG. 1 shows another example of a perovskite solar cell according to the present invention in which a single-walled carbon nanotube (SWNTs) net synthesized in a vertical thermal CVD apparatus is used as a transparent conductive electrode. [Diagram 3] Synthesis of single-walled carbon nanotube thin film using vertical thermal CVD equipment [Figure 4] A diagram showing the manufacturing process of the perovskite solar cell shown in Figure 2. [Diagram 5] SEM image of single-walled carbon nanotube net [Figure 6] TEM image of single-walled carbon nanotube net [Figure 7] Raman spectroscopy of single-walled carbon nanotube network [Figure 8] Diagram of the purification of single-walled carbon nanotube net attached to protective glass DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] A protective glass is placed at the bottom of a vertical thermal CVD apparatus with an electric furnace installed around its periphery, and the temperature of the electric furnace in the vertical thermal CVD apparatus is set to 800°C to 1000°C. A mixed liquid of Fe / ethanol is sprayed from a nebulizer device to synthesize single-walled carbon nanotubes onto the protective glass, resulting in a perovskite solar cell in which one or more single-walled carbon nanotubes each serve as a transparent conductive electrode. EXAMPLES
[0018] (Synthesis of single-walled carbon nanotubes) FIG. 3 shows a vertical thermal CVD apparatus using a quartz tube for producing a single-walled carbon nanotube (SWNTs) net 2 (2a, 2b), in which an electric furnace 10 is provided around the outside of the quartz tube, protective glass 1 (1a, 1b) is placed on a table 19 provided at the bottom of the apparatus below the electric furnace 10, and a nebulizer device 11 is further provided inside the cylinder containing a mixture of iron-based metal and lower alcohol, preferably a mixture 16 of Fe / ethanol.
[0019] When producing a single-walled carbon nanotube (SWNTs) net 2 (2a, 2b), the vacuum pump 14 is started to draw a vacuum, and then the N2 gas valve 13 is turned ON to remove the air from within the thermal CVD chamber. The temperature is raised to the synthesis temperature (800°C to 1000°C), and finally the nebulizer device 11 is turned ON to evaporate the Fe / ethanol mixture 16. This causes the Fe / ethanol mixture 16 to become atomized and pass through the heating part of the electric furnace 10 to synthesize the SWNTs net 2 on the protective glass 1 (about 100°C).
[0020] Figure 1 shows an example of a perovskite solar cell in which a single-walled carbon nanotube (SWNTs) net synthesized in a vertical thermal CVD apparatus is used as a transparent conductive electrode. Figure 1 shows a perovskite solar cell showing one embodiment of the present invention, in which the synthesized SWNTs 2 are attached to a protective glass 1 to form a transparent conductive electrode. Next, a hole transition layer (conductive polymer: PEDOT:PSS) 3, a conductive layer (Poly TPD) 4 in which holes flow and electrons are blocked, a perovskite layer 5, a conductive layer (PCBM) 6 in which electrons flow and holes are blocked, and a metal electrode 7 are laminated in this order, and finally the SWNTs 2 and the metal electrode 7 are connected using wiring 8 to form the structure of the perovskite solar cell.
[0021] In the solar cell manufacturing process of FIG. 1, a single-walled carbon nanotube (SWNTs) net 2 is synthesized on a protective glass 1 as described above.
[0022] Next, a hole transition layer (conductive polymer: PEDOT:PSS) 3, a conductive layer (Poly TPD) 4 that allows holes to flow and blocks electrons, and a perovskite layer 5 are coated.
[0023] The perovskite layer 5 is coated with a conductive layer (PCBM) 6 that allows surface electrons to flow and blocks holes, and then a metal electrode 7 is laminated on top of it. Finally, the single-walled carbon nanotube (SWNTs) net 2 and the metal electrode 7 are connected using wiring 8 to form the structure of the perovskite solar cell.
[0024] When exposed to sunlight 9, electrons-holes are excited in the perovskite layer 5, and since the hole transition layer 3 has a low carrier transition rate, the diffusion distance and lifetime of the carriers are increased.
[0025] The electron-hole pairs that do not recombine are collected in the electron conducting layer (PCBM) 6 and the hole conducting layer (Poly TPD) 4, and finally flow into the conductive electrode, generating a current. EXAMPLES
[0026] 2 shows another example of a perovskite solar cell in which a single-walled carbon nanotube (SWNTs) net synthesized in a vertical thermal CVD apparatus is used as a transparent conductive electrode, and the single-walled carbon nanotube (SWNTs) net 2 synthesized in the vertical thermal CVD apparatus forms a transparent conductive electrode coated on a protective glass 1. Next, a perovskite material 5, a single-walled carbon nanotube (SWNTs) net 2, a perovskite material 5, and a metal (Au) electrode 7 are laminated in this order, and finally the SWNTs 2 and the metal (Au) electrode 7 are connected using wiring 8.
[0027] The manufacturing process of the perovskite solar cell shown in FIG. 2 using the single-walled carbon nanotube (SWNTs) net 2 (2a, 2b) produced using the vertical thermal CVD apparatus described above will be described with reference to FIG.
[0028] [Step shown in FIG. 4A] First, two protective glasses 1a and 1b are prepared on a liftable table 19. The protective glasses 1a and 1b are used in the structure of this perovskite solar cell to prevent impurities such as dirt and dust. On the other hand, the protective glass 1b is used when transferring to the perovskite layer 5a.
[0029] [Step shown in FIG. 4B] A SWNT net 2a is coated on a protective glass 1a in a vertical thermal CVD apparatus to form a transparent and conductive electrode. For example, the mobility of SWNT electrons with a diameter of Φ1.5 nm is approximately 36,000 cm at room temperature. 2 / Vs, achieving a light transmittance of 92%.
[0030] [Step shown in FIG. 4C] The SWNTs net 2a synthesized on the protective glass 1a is washed with water vapor generated by a nebulizer device, dried, and then a perovskite layer 5a is applied thereon.
[0031] [Step shown in FIG. 4D] By immersing the protective glass 1b with the SWNTs net in purified water 12, the surface 1b of the protective glass is oxidized, thereby decreasing the adhesion to the SWNTs net 2b.
[0032] [Step shown in FIG. 4E] A thermal peeling tape 17 is pressed onto the synthesized SWNTs 2b on the protective glass 1b.
[0033] [Step shown in FIG. 4F] The SWNTs net 2b is peeled off from the protective glass 1b by means of a thermal peeling tape 17.
[0034] [Step shown in FIG. 4G] The exfoliated SWNTs network 2b is transferred to the perovskite layer 5a.
[0035] [Step shown in FIG. 4H] Weaken the adhesive strength of tape 17.
[0036] [Step shown in FIG. 4I] The heated thermal peeling tape 17 is removed by the protective glass 1b.
[0037] [Step shown in FIG. 4J] The SWNTs net is transferred to the perovskite layer 5a.
[0038] [Step shown in FIG. 4K] A perovskite layer 5b is applied to the transferred SWNTs net.
[0039] [Step shown in FIG. 4L] A metal (Au) 7 is coated onto the perovskite layer 5b.
[0040] [Step shown in FIG. 4G] Metal conductors 8 are wired between the transparent conductive electrode SWNTs nets 2a, 2b and the Au metal electrode 7. The multi-layer perovskite solar cell constructed as above is operated by irradiation with light 9. and multi-layer perovskite solar cells are powered by light exposure.
[0041] In addition, the above embodiment shows an example in which the perovskite solar cell structure according to the present invention is a multi-layer structure as shown in FIG. 2. However, in the present invention, since the single-walled carbon nanotube (SWNTs) net (2) is very thin and has excellent light transmission effect, it can be made into a multi-layer laminate structure in principle, which can significantly improve the photoelectric conversion rate of the perovskite solar cell.
[0042] However, the present invention is of course not limited to the above-described embodiment, and various modifications are possible within the scope of the claims.
[0043] (Purification of single-walled carbon nanotubes) The problem of amorphous carbon and dust that occurs during the synthesis of single-walled carbon nanotubes can be addressed by moving the protective glass 1 placed on the table 19 to the electric furnace 7 as shown in Figures 8(a) and (b), spraying the purified water from the nebulizer onto the protective glass 1, and then drying at 100 to 150°C about three times. This completely removes the amorphous carbon and dust from the CNTs net (2) as shown in Figures 8(c) and (d) and (e), and the spaces between the nanotubes of the CNTs net (2) naturally expand significantly, thereby increasing the light transmittance of this transparent conductive electrode (6).
[0044] (Verification of single-walled carbon nanotubes) Figure 5. (a) and (b) are SEM images of the SWNTs net. A thin SWNTs net is observed on the protective glass, and it is clear that a very large amount of SWNTs has been synthesized in the form of a net.
[0045] Figure 6 (a) and (b) are TEM images of the SWNTs net. Planar TEM observation was performed to confirm the distribution of SWNTs. Numerous CNTs extending in a net-like shape from the SWNTs are clearly observed. It is believed that this net plays a role in imparting electrical conductivity.
[0046] Figure 7 shows the Raman spectrum of the single-walled carbon nanotube net. The Raman spectrum of the single-walled carbon nanotube contains a peak at 1,340 cm -1 A vibration mode called the D-band is observed near the 1,340 cm peak. This mode is not observed in graphite with good crystallinity because it is not Raman active, but if the symmetry is disturbed by the introduction of defects, it is observed as a Raman peak. For this reason, the amount of defects can be evaluated using the peak intensity ratio (G / D ratio) between the D-band and the G-band, which is a vibration mode of the same type as the Raman active mode of graphite. A material with a high G / D ratio is considered to have fewer defects and higher quality. Figure 6 shows the amount of defects at 1,340 cm. -1 The D-band was observed near 1,600 cm -1 The G-band is observed near the 1,590 cm -1 By calculating the peak intensities of the G-band and D-band near the center, the G / D ratio (G-band intensity / D-band intensity) was calculated to be G / D = 3.286. This suggests that the G / D ratio indicates a small number of defects, and that the number of defects in the nanotubes produced by this process is also small.
[0047] As described above, the transparent conductive electrode used in the solar cell of the present invention can be replaced with a carbon nanotube thin film, which has excellent flexibility, conductivity and light transmittance compared with the commonly used ITO glass, and is significantly thinner and has excellent bending and deformation properties. Therefore, it not only has the advantages of low resistance and high light transmittance, but also reduces the weight of the entire solar cell. [Industrial Applicability]
[0048] According to the present invention, by constructing a transparent conductive electrode from single-walled carbon nanotubes, it is possible to provide a perovskite solar cell which has advantages such as excellent flexibility, conductivity, and light transparency, as well as being thin, lightweight, and resistant to bending and deformation. [Explanation of symbols]
[0049] 1(1a,1b)…………Protective glass 2(2a,2b)………Single-walled carbon nanotube net 3...Transparent conductive polymer (PEDOT:PSS) 4……………Poly TPD 5(5a,5b)…Perovskite layer 6....PCBM 7…………Metal (Au) 8…………Wiring 9………… light 10....Electric furnace 11...Nebulizer device 12…………Purified water 13....N2 gas valve 14...Vacuum pump 15...Water vapor 16: Fe / ethanol mixture 17...Heat release tape 18…………Ultraviolet heating 19…………Table
Claims
1. A protective glass is placed at the bottom of a vertical thermal CVD apparatus with an electric furnace installed around the periphery, and the temperature of the electric furnace in the vertical thermal CVD apparatus is set to 800°C to 1000°C. A nebulizer device is used to spray a mixture of Fe-based element metal / alcohol onto the protective glass to synthesize one or more single-walled carbon nanotubes, each of which serves as a transparent conductive electrode to form a perovskite solar cell.
2. 2. The perovskite solar cell according to claim 1, wherein the perovskite solar cell is configured by coating a perovskite material layer on each of two or more transparent conductive electrodes made of single-walled carbon nanotubes.
3. 2. The perovskite solar cell according to claim 1, wherein the single-walled carbon nanotubes synthesized on the protective glass are sprayed and washed with purified water from a nebulizer device in a vertical thermal CVD apparatus, and then dried.
4. 2. The perovskite solar cell according to claim 1, wherein the mixed solution of Fe-based element metal / alcohol is a mixed solution of Fe / ethanol.
5. 3. A method for producing a perovskite solar cell according to claim 2, further comprising the steps of: providing a protective glass and one or more transfer protective glasses at the bottom of a vertical thermal CVD apparatus having an electric furnace installed around its periphery; setting the temperature of the electric furnace in the vertical thermal CVD apparatus to 800°C to 1000°C; atomizing a mixed liquid of Fe-based element metal / alcohol from a nebulizer device and letting it flow down from the top of the vertical thermal CVD apparatus to form single-walled carbon nanotubes on the protective glass or the transfer protective glass; coating the single-walled carbon nanotubes formed on the protective glass with a perovskite material layer; peeling off the single-walled carbon nanotubes formed on the transfer protective glass and transferring them to the perovskite material layer; and coating the transferred single-walled carbon nanotubes with a perovskite layer, repeated at least twice.
6. 6. The method according to claim 5, wherein the single-walled carbon nanotubes formed on the protective glass or the transfer protective glass are washed by spraying purified water from a nebulizer device in a vertical thermal CVD apparatus, and then dried.
7. 6. The method according to claim 5, wherein the mixed solution of Fe-based element metal / alcohol is a mixed solution of Fe / ethanol.